How robust is the language architecture? The case of mood - Van Berkum, Jos J.; de Goede, Dieuwke; van Alphen, Petra; Mulder, Emma; Kerstholt, Jose H. (Frontiers in Psychology, 2013)
In neurocognitive research on language, the processing principles of the system at hand are usually assumed to be relatively invariant. However, research on attention, memory, decision-making, and social judgment has shown that mood can substantially modulate how the brain processes information. For example, in a bad mood, people typically have a narrower focus of attention and rely less on heuristics. In the face of such pervasive mood effects elsewhere in the brain, it seems unlikely that language processing would remain untouched. In an EEG experiment, we manipulated the mood of participants just before they read texts that confirmed or disconfirmed verb-based expectations about who would be talked about next (e.g., that "David praised Linda because..." would continue about Linda, not David), or that respected or violated a syntactic agreement rule (e.g., "The boys turns"). ERPs showed that mood had little effect on syntactic parsing, but did substantially affect referential anticipation: whereas readers anticipated information about a specific person when they were in a good mood, a bad mood completely abolished such anticipation. A behavioral follow-up experiment suggested that a bad mood did not interfere with verb-based expectations per se, but prevented readers from using that information rapidly enough to predict upcoming reference on the fly, as the sentence unfolds. In all, our results reveal that background mood, a rather unobtrusive affective state, selectively changes a crucial aspect of real-time language processing. This observation fits well with other observed interactions between language processing and affect (emotions, preferences, attitudes, mood), and more generally testifies to the importance of studying ‘cold’ cognitive functions in relation to ‘hot’ aspects of the brain.